2016
DOI: 10.3727/096368916x691439
|View full text |Cite
|
Sign up to set email alerts
|

PDGF Facilitates Direct Lineage Reprogramming of Hepatocytes to Functional β-Like Cells Induced by Pdx1 and Ngn3

Abstract: Islet transplantation has been proven to be an effective treatment for patients with type 1 diabetes, but a lack of islet donors limits the use of transplantation therapies. It has been previously demonstrated that hepatocytes can be converted into insulin-producing b-like cells by introducing pancreatic transcription factors, indicating that direct hepatocyte reprogramming holds potential as a treatment for diabetes. However, the efficiency at which functional b-cells can be derived from hepatocyte reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Notably, the release of the EGF, proved to be an enhancer of fibroblast proliferation and, as consequence, of impairing cell reprogramming, was significantly lower in culture of slow‐proliferating dermal fibroblast from abdominal skin and significantly higher in culture of fast‐proliferating fibroblasts from arm skin. On the contrary, the release of growth factors known to be inducers of cell reprogramming, like GM‐CSF, HGF, PDGF and VEGF resulted significantly higher in dermal fibroblasts from abdominal skin (Figure ). Furthermore, as reprogramming of fibroblasts to iPSCs requires a mesenchymal to epithelial transition (MET), factors involved in the activation of MET or inhibition of the opposite process, the epithelial‐to‐mesenchymal transition (EMT), have potential critical role in reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the release of the EGF, proved to be an enhancer of fibroblast proliferation and, as consequence, of impairing cell reprogramming, was significantly lower in culture of slow‐proliferating dermal fibroblast from abdominal skin and significantly higher in culture of fast‐proliferating fibroblasts from arm skin. On the contrary, the release of growth factors known to be inducers of cell reprogramming, like GM‐CSF, HGF, PDGF and VEGF resulted significantly higher in dermal fibroblasts from abdominal skin (Figure ). Furthermore, as reprogramming of fibroblasts to iPSCs requires a mesenchymal to epithelial transition (MET), factors involved in the activation of MET or inhibition of the opposite process, the epithelial‐to‐mesenchymal transition (EMT), have potential critical role in reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that expression of pancreatic pdx 1 and insulin was upregulated in diabetic animals transplanted with islet with PRP and biomaterial combination therapy. Several studies have indicated that treatment INS-1 with TGF- β [ 60 ] and pancreatic β -cell with PDGF-AA [ 61 ] or ECM proteins (28) could increase pdx 1 and insulin mRNA expressions. The other study showed that laminin could increase the expression levels of islet-specific genes such as pdx1 and insulin [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of PDX1 and Ngn3 induces the expression of various islet cell‐specific genes to initiate a series of events that induce a small number of hepatocytes into β‐like cells. Chang et al showed that PDX1 and Ngn3 combined can reprogram hepatocytes into platelet‐derived growth factor receptor A (PDGFRα)‐positive β‐like cells 31 . The addition of PDGF‐AA to glucagon‐like peptide‐1/exendin‐4‐containing medium promotes the expansion of β‐like cells, and the cells can secrete insulin in response to glucose stimulation, enabling the treatment of diabetic mice after transplantation.…”
Section: Gene Reprogramming Technology Of Hepatocytes In Pancreatic R...mentioning
confidence: 99%
“…Chang et al showed that PDX1 and Ngn3 combined can reprogram hepatocytes into platelet‐derived growth factor receptor A (PDGFRα)‐positive β‐like cells. 31 The addition of PDGF‐AA to glucagon‐like peptide‐1/exendin‐4‐containing medium promotes the expansion of β‐like cells, and the cells can secrete insulin in response to glucose stimulation, enabling the treatment of diabetic mice after transplantation. Compared to previous work using PDX1 alone to reprogram hepatocytes into insulin‐producing cells, the improved strategy developed based on the current work not only improves the efficiency of reprogramming hepatocytes into β‐like cells but also enhances the ability of reprogrammed cells to secrete insulin.…”
Section: Gene Reprogramming Technology Of Hepatocytes In Pancreatic R...mentioning
confidence: 99%